Effects of tropical cyclone Freddy on the social determinants of health: the narrative review of the experience in Malawi - Braka, Fiona; Daniel, Ebenezer Obi; Okeibunor, Joseph; Rusibamayila, Neema Kimambo; Conteh, Ishata Nannie; Ramadan, Otim Patrick Cossy; Byakika-Tusiime, Jayne; Yur, Chol Thabo; Ochien, Emmanuel Maurice; Kagoli, Mathew; Chauma-Mwale, Annie; Chamla, Dick; et al. (BMJ public health, 2024)
Malawi—one of the low-income countries in Africa—has witnessed a series of flood-related disasters in many years. The recent tropical cyclone Freddy (TCF) has indispensable effects on the unequal distribution of the social determinants of health with tendencies for increased disease outbreaks across the districts of the country. This narrative study aimed at unravelling the consequences of the TCF and its possible relationship with the already existing cholera epidemic in the fourteen affected districts. Additionally, it aimed to document the immediate humanitarian responses in the acute phase of the disaster. We identified, used and extracted information and data from relevant documents available from the government records, WHO and other multiagency documents, which were summarised along with the humanitarian actions and the associated implications of the entire event. Areas of TCF’s main effects included health, shelter, education, nutrition, water sanitation and hygiene, agriculture and livelihood, transport and logistics including food security. The notable immediate humanitarian responses are donations, camp creation for accommodations, emergency life-saving response and essential healthcare services. Nsanje and Chikwawa districts experienced an increase in cholera cases and deaths post-TCF. The highest proportion of the disaster-impacted and intervention beneficiaries were women and children. The effects of the TCF on the social determinants of health in the affected districts and the associated negative impacts should be considered by the government and disaster management experts in evidence-based policy-making towards disaster risk reduction in the flood-prone districts using an all-hazard approach. This step might be useful in improving the vulnerable population’s standard of living and achievement of related Sustainable Development Goals in Malawi.